Penguatan Konsep Mu’amalah dan Kewirausahaan untuk Membangun Kemandirian Ekonomi Santri - Qomaro, Galuh Widitya; Dzikrulloh, Dzikrulloh; Hanifah, Luluk; Rahman, Taufiqur; Sunariyah, Anik; Nasik , Khoirun (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
This community service program aims to build independence and entrepreneurial character among the students of Pondok Pesantren Nurul Amanah Bangkalan through the Asset-Based Community Development (ABCD) approach. The activity involved 10th and 11th-grade students in entrepreneurship training based on the pesantren's business units, such as Bakso Gibras, Nasi Ayam Chili Padi, AMDK, mushroom cultivation, and catfish farming. The methods used include theoretical training on mu'amalah in the context of sharia entrepreneurship and hands-on experience in the pesantren's business units. The results show that the students actively participated in the operations of these businesses and were able to identify opportunities and challenges in managing the businesses. With the ABCD approach, the students gained not only entrepreneurial skills but also social and religious values that support the economic development of the pesantren. This program successfully contributed to the empowerment of the students while developing the pesantren's business units as a sustainable learning tool.